The Effect of Self-Efficacy on Academic Resilience through Subjective Well-Being as a Mediator Variable in Public High School Students in Tarakan City - Saputri Sri Lestari; Nanang Erma Gunawan (Journal of Educational Sciences, 2026)
High school students encounter increasing academic demands that require not only strong academic competence but also psychological resources to adapt and persist in learning. Self-efficacy has been recognized as an important predictor of academic resilience; however, the mediating role of subjective well-being in this relationship remains inconclusive. This study aimed to examine the direct effect of self-efficacy on academic resilience and to investigate whether subjective well-being mediates this relationship among senior high school students in Tarakan City. This study employed a quantitative explanatory design involving 367 senior high school students selected through purposive random sampling from a population of 4,422 students. Data were collected using validated self-efficacy, subjective well-being, and academic resilience scales and analyzed using path analysis and the Sobel test. The findings revealed that self-efficacy significantly predicted both subjective well-being and academic resilience, while subjective well-being also had a significant positive effect on academic resilience. However, subjective well-being did not significantly mediate the relationship between self-efficacy and academic resilience. These findings indicate that self-efficacy contributes directly to strengthening students' academic resilience, whereas subjective well-being functions as an independent psychological factor rather than a mediating mechanism. This study provides empirical evidence that can inform the development of school-based interventions aimed at enhancing students' resilience through the improvement of self-efficacy.